Under-reporting of sexually transmitted infection with chlamydia trachomatis - a revision of surveillance system is required - Kustec Tanja; Keše Darja; Klavs Irena (Sciendo, 2016)
To consider whether a revision of the national chlamydia surveillance system is needed, the objectives were to estimate the proportion of laboratory confirmed cases at the Institute of Microbiology and Immunology (IMI) not reported to the National Institute of Public Health (NIPH), and to assess the completeness of reporting for individual data items.